Deleuze and ethics - Jun, Nathan J. 1979-; Smith, Daniel W. 1958- (Edinburgh University Press, 2011)
Deleuze is perhaps best known for his influential works in philosophical interpretation; epistemology; metaphysics; and political economy. The essays in this collection explore uncover and trace the ethical dimension of Deleuzian philosophy along diverse trajectories and in so doing endeavour to reclaim that philosophy as moral philosophy